2008
DOI: 10.1111/j.1751-9020.2008.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Homicide Arrest Clearances: A Review of the Literature

Abstract: This is a review of the research literature on homicide arrest clearances or homicides for which no offender is arrested. The article describes the decline in the percent of homicides resulting in arrests and charges from over 90 pecent in 1960 to 61 percent in 2006. Research is reviewed on the reasons for the lack of public attention and concern and the low homicide clearance rates in the USA in comparison with other countries. Research on the extent to which homicides are uncleared because they involve low‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 27 publications
(72 reference statements)
6
111
1
7
Order By: Relevance
“…14 The literature strongly suggests that incident-level characteristics such as victim's demographics and the incident's situational characteristics are also important factors in the clearance outcome (e.g. Litwin 2004;Lundman and Myers 2012;Puckett and Lundman 2003;Riedel 2008;Roberts 2007). 15 Based on Black's (1976) influential work on the behavior of law, the victim-devaluing or extralegal perspective argues that allocation of police investigative time and effort varies by the victim's extralegal characteristics.…”
Section: Incident-level Control Variablesmentioning
confidence: 98%
“…14 The literature strongly suggests that incident-level characteristics such as victim's demographics and the incident's situational characteristics are also important factors in the clearance outcome (e.g. Litwin 2004;Lundman and Myers 2012;Puckett and Lundman 2003;Riedel 2008;Roberts 2007). 15 Based on Black's (1976) influential work on the behavior of law, the victim-devaluing or extralegal perspective argues that allocation of police investigative time and effort varies by the victim's extralegal characteristics.…”
Section: Incident-level Control Variablesmentioning
confidence: 98%
“…For homicides, these characteristics relate to the available evidence and are measured in terms of weapons (with firearms less likely to leave evidence than personal weapons), victim-offender relationship (with known offenders being easier to identify and arrest than strangers), and location (with home locations serving to protect crime scene evidence and suggest possible offenders as compared to other or outside locations; Riedel, 2008). This extralegal framework is not supported in the homicide literature regarding age and sex as clearances more often occur in cases involving young victims, especially children, and females (both hypothesized as lower status groups) rather than older victims and males (see Riedel, 2008, for a summary). With regard to race, mixed support has been obtained for Black's hypothesis that fewer arrests will be made for minority race victims and more for minority race offenders (Riedel, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Lower clearance rates are puzzling because declines have occurred during a time when the number of homicides in the United States is dropping and there is potentially more available detective time to work cases, more technological advances that should enhance detection and investigation, and increased incarceration rates. Riedel (2008) has noted a lack of public attention to declining homicide clearance rates and suggested that police department reluctance to share information about cases with the public or academics may be a contributing factor. Some research suggests the changing nature of homicides (e.g., more gang, drugrelated, and stranger homicides) has reduced clearance rates (Regoeczi, Kennedy, & Silverman, 2000).…”
Section: Introductionmentioning
confidence: 99%